The Risk of Perioperative Bleeding in Patients with Dual Antiplatelet Therapy - Domanskyy, Taras M.; Gabriyelyan, Artur V.; Beregovoy, Oleg V.; Filianin, Stanislav I.; Moshta, Svitlana S. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Background. Patients with dual antiplatelet therapy have high risk of perioperative bleeding. In this article we evaluated the risk of bleeding in patients whose antiplatelet therapy had not been canceled before coronary artery bypass grafting (CABG). The aim. To investigate and evaluate the risk of intra- and postoperative bleeding in patients who underwent CABG during antiplatelet therapy. Materials and methods. In the study, 47 case reports of patients with coronary heart disease who underwent CABG were evaluated. The patients were divided into 2 groups. The first group included 26 patients who discontinued antiplatelet therapy less than 5 days before the operation. The second group included 21 patients who discontinued antiplatelet therapy more than 5 days before the operation. Stratification of the risk of bleeding was performed using HAS-BLED Score for Major Bleeding Risk online calculator. Results and discussion. The major bleeding risk was 5.1 ± 1.4% and 4.4 ± 1.6% in the first and in the second group, respectively. In spite of higher risk of bleeding in the first group, there was no significant difference in intra- and postoperative bleeding complications. Conclusions. Candidates for surgical intervention who receive dual antiplatelet therapy have high risk of intra- and postoperative bleeding complications. In urgent cases when timely discontinuation of dual antiplatelet therapy is impossible and there is urgent need in the intervention, the latter must be performed. For patients who were prepared for CABG and discontinued dual antiplatelet therapy less than 5 days before the operation, sufficient volume of blood for transfusion must be provided.